1999
DOI: 10.1038/sj.onc.1202585
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the DPC4/Smad4 gene in neuroendocrine pancreatic tumors

Abstract: Tumors of the endocrine pancreas are extremely rare, and molecular mechanisms leading to their development are not well understood. A candidate tumor suppressor gene, DPC4, located at 18q21, has recently been shown to be inactivated in half of pancreatic adenocarcinoma xenografts. The close anatomical relationship of the exocrine and endocrine pancreas prompted us to determine the role of DPC4 in the tumorigenesis of 25 pancreatic islet cell tumors (11 insulinomas, nine nonfunctioning endocrine carcinomas, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 15 publications
1
58
1
1
Order By: Relevance
“…Only exons 8 -11 were sequenced since the majority of previously described mutations have been found in this region. 15 The results revealed no mutations, and immunohistochemical staining showed expression of the Smad4/ DPC4 protein in the 7 analyzed tumors (data not shown). Tumor 5216 was not analyzed by immunohistochemical staining due to a shortage of tissue material.…”
Section: Resultsmentioning
confidence: 89%
“…Only exons 8 -11 were sequenced since the majority of previously described mutations have been found in this region. 15 The results revealed no mutations, and immunohistochemical staining showed expression of the Smad4/ DPC4 protein in the 7 analyzed tumors (data not shown). Tumor 5216 was not analyzed by immunohistochemical staining due to a shortage of tissue material.…”
Section: Resultsmentioning
confidence: 89%
“…Chromosome 18 harbors several candidate tumor suppressor genes, including DCC, SMAD4, and SMAD2. Interestingly, 55% of nonfunctioning pancreatic endocrine carcinomas had point mutations or deletion of SMAD4 gene (Bartsch et al, 1999), but no SMAD4 mutations were identified in classical midgut WDNTs (Lö llgen et al, 2001) and goblet cell carcinoids of the vermiform appendix (Stancu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of SMAD4 gene mutations in human cancer occur at the MH2 domain (17). In pancreatic cancer, somatic mutational events occur with high frequency (2,18,19). In total, approximately 55% of pancreatic cancers show inactivation of the SMAD4 gene (17).…”
Section: -------------------------------------------------Size Of Primentioning
confidence: 99%